Komunikasi Pemerintah Provinsi Jawa Barat dalam Pengembangan Kawasan Wisata Geopark Ciletuh Palabuhanratu di Kabupaten Sukabumi - Dinata, Mochamad Fattahidayah; Muradi, Muradi; Kartini, Dede Sri (Jurnal Politikom Indonesiana, 2018)
The present study discusses the communication process conducted by the Provincial Government of West Java with the citizens of Ciletuh, Palabuhanratu in supporting the development undergone in the Geopark tourism area. The study uses qualitative method with descriptive approach. The theory consulted for the purpose of the study is that of Public Relation in six steps, namely: identifying the problem, determining the target, determining the public, planning the program, executing the program and evaluating the results. The findings indicate that the communication between the government and the its people is less effective due to the presence of disbelief between the communicators and interlocutors (people), the less-distributed information, and the non-cooperative attitude of the village government when conducting advanced socialization. Therefore, the occuring communication has not well improved the informative and motivative target of the public. Keywords: Governmental communication, public relation, tourism area development